Evaluasi Pembiayaan Perumahan Akad Murabahah Versus Kredit Konvensional Berdasarkan Volatilitas Harga - Sahlan Hasbi; Kuncoro Hadi (Journal of Accounting and Investment, 2016)
The purpose of this study was to determine whether the pattern of housing financing murabaha or conventional mortgages can overcome the volatility of house prices after the maturity of the financing. The data used is the housing finance murabaha installment in Bank Syariah Mandiri and Bank BRISyariah and conventional housing loan installment consumer loan interest is based on the National Private Bank. The study says that housing finance murabaha at bank Syariah Mandiri, Bank BRISyariah and conventional mortgages experienced a capital loss caused due to the volatility of house prices where the market value of the home after the maturity of the financing is higher than the value of the house based on murabaha financing and conventional loans.